ANALISIS KONSEPSI DAN MAKNA BUSANA SANTRI PUTRA PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO - Moch. Nuril Anwar; Edy Supriyono (Fakultas Dakwah Universitas Ibrahimy, 2025)
This article reveals the concept of Islamic boarding schools towards the clothing of students at the Salafiyah Syafi'iyah Sukorejo Situbondo Islamic Boarding School and the meaning of communication of clothing used by some students that do not meet customary norms. Islamic boarding schools are the oldest educational institutions in Indonesia that still exist and consistently teach and practice Islamic teachings. Including one of them about the practice of student clothing. In 2016, the author saw at the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School there was a phenomenon of the clothing style of some students that did not comply with customary norms of the Islamic boarding school. The portrait of the clothing style of male students was seen to be influenced by foreign culture. Especially those that dominate European clothing styles or what are Vol. 7 No. 1 Januari 2025263 | J U R N A L K O M U N I K A S I D A N K O N S E L I N G I S L A Moften known as western clothing styles. Starting from clothes (t-shirts) with skull pictures, pictures of women without hijab, wearing pencil pants and also some wearing necklaces. Even though the Islamic boarding school has provided clear rules and is reinforced by a circular from the Islamic boarding school management. This study focuses on qualitative data processing with field research. This type of research is descriptive, describing research questions that contain answers about the phenomenon of the dress code of male students of the Salafiyah Syafi'iyah Sukorejo Situbondo Islamic Boarding School in 2016. The results are that the minimum standard of dress of students of the Salafiyah Syafi'iyah Sukorejo Situbondo Islamic Boarding School is 3, namely covering the aurat, not tasabbuh and following the norms of the pesantren. The meaning of communication displayed by students who do not wear clothes according to the norms of the pesantren is 2, namely depicting identity and imitating because of trends.